Development of HOTS-Based Independent Curriculum Science Module in Class VI SDN 17 Banda Aceh - Lindayani, Lindayani; Kasmini, Lili; Syarfuni, Syarfuni; Putra, Mulia; Syafii, Mhd.; Zubairi, Muhammad Zulhairi Bin (Jurnal Pendidikan Humaniora, 2025)
This research aims to develop a HOTS-based Merdeka Curriculum science module for class VI SDN 17 Banda Aceh in accordance with the Merdeka Curriculum. The development method used is Research and Development (R&D), namely using the ADDIE model to produce certain products and testing the effectiveness of these products. This research involved 25 class VI students at SDN 17 Banda Aceh and one teacher as respondents. The research instruments used were validation questionnaires and observation sheets. Analysis techniques are used to determine the feasibility of the science module that has been assessed. The results of the research show that the HOTS-based science module developed has a level of validity, namely the first validator for the language aspect is 82%, the design aspect is 82%, and the material aspect is 80%, while the second validator is the language aspect 86%, the design aspect is 89%, and the material aspect is 89%. The evaluation question test validated its effectiveness with scores of 94% and 86%. The implication of this research is that the module developed can be used as an effective learning resource to improve students' high-level thinking abilities in science learning at SDN 17 Banda Aceh. Apart from that, this research also contributes to the development of a curriculum that is relevant to the needs of the times and current global challenges.